2021
DOI: 10.1016/j.jbc.2021.101141
|View full text |Cite
|
Sign up to set email alerts
|

Ribosylation of the CD8αβ heterodimer permits binding of the nonclassical major histocompatibility molecule, H2-Q10

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Indeed, CD8 expression is regulated transcriptionally ( Bosselut et al, 2003 ; Park et al, 2007 ) and by modulation at the cell surface ( Maile et al, 2005 ; Xiao et al, 2007 ). In addition, post-translational modifications of CD8αα and CD8αβ proteins can alter their ability to bind MHC-Ia molecules ( Daniels et al, 2001 ; Moody et al, 2001 ; Kao et al, 2006 ; Lischke et al, 2013 ) and MHC-Ib molecules, as recently demonstrated for H2-Q10 ( Goodall et al, 2021 ). It is also known that CD8αα can be induced on IELs, conventional T cells, and immature thymocytes in response to microenvironmental cues and TCR stimulation ( Reis et al, 2013 ; Gangadharan and Cheroutre, 2004 ).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, CD8 expression is regulated transcriptionally ( Bosselut et al, 2003 ; Park et al, 2007 ) and by modulation at the cell surface ( Maile et al, 2005 ; Xiao et al, 2007 ). In addition, post-translational modifications of CD8αα and CD8αβ proteins can alter their ability to bind MHC-Ia molecules ( Daniels et al, 2001 ; Moody et al, 2001 ; Kao et al, 2006 ; Lischke et al, 2013 ) and MHC-Ib molecules, as recently demonstrated for H2-Q10 ( Goodall et al, 2021 ). It is also known that CD8αα can be induced on IELs, conventional T cells, and immature thymocytes in response to microenvironmental cues and TCR stimulation ( Reis et al, 2013 ; Gangadharan and Cheroutre, 2004 ).…”
Section: Discussionmentioning
confidence: 94%
“…For example, Pydc4 , Rhov , Oasl1 , Hdc , Isg15 , Il1f9 , Saa3 , Ccl4 , Treml2 , H2‐Q10 , and Cebpe in primary tumors and Ly6c2 , CD8b1 , Gimap5 , Lat , Hcst , Cd3d , Pglyrp1 , Tusc5 and H2‐Q10 in abscopal tumors were significantly downregulated with the absence of TDLN. Because most of these genes are associated with T cell function [ 35 , 36 , 37 , 38 ], the finding indicated that the removal of bilateral TDLN might lead to impaired iRT‐induced T cell responses.…”
Section: Resultsmentioning
confidence: 99%